Effects of feeding mycotoxin-contaminated diets and the use of a yeast cell wall extracts mycotoxin adsorbent on ruminal and fecal microbiota of finishing beef steers - Batista, Luis Henrique Cursino; Granja-Salcedo, Yury Tatiana; Ferreira, Igor Machado; Souza, Mailza Gonçalves de; Abreu, Mateus José Inácio de; Costa e Silva, Luiz Fernando; Koontz, Anne; Holder, Vaughn; Pettigrew, James Eugene; Siqueira, Gustavo Rezende; Resende, Flávio Dutra de (Frontiers in Microbiology, 2025)
IntroductionThis study evaluated the effects of contamination of the beef cattle diet with mycotoxins and the use of yeast cell wall extract based mycotoxin adsorbent(YCWE) on the ruminal and fecal microbial communities.MethodsEight rumen-cannulated Nellore steers [initial body weight (BW) = 417 ± 42 kg; ± 36 month of age] were used in a 4 × 4 replicated Latin square design. A 2 × 2 factorial treatment structure was used to investigate the effects of mycotoxin contamination of the diet, the addition of YCWE and their interactions. The dietary treatments consisted of: (1) diet without mycotoxins (CTRL), and (2) control diet with added mycotoxins(MYCOT). The second factor was: (1) absence (YCWE−) or (2) presence (YCWE+)of YCWE. The addition of YCWE to the diets was 1 g/kg of dry matter (DM).ResultsIn the rumen, MYCOT increased microbial richness and diversity indices (p < 0.01), whereas YCWE decreased richness but increased diversity (p < 0.01). MYCOT contamination also increased the relative abundance of taxa associated with inefficient nitrogen utilization (p < 0.08). YCWE supplementation affected several microbial groups, reducing the abundance of methanogenic archaea and acetateproducing bacteria (p < 0.02). Predicted metabolic pathways indicated that MYCOT impaired several functions related to microbial growth and protein synthesis, while YCWE supplementation in contaminated diets partially restored pathways such aspurine and pyrimidine metabolism (p < 0.05). However, YCWE supplementation inuncontaminated diets reduced pathways linked to protein synthesis (p < 0.05). In feces, MYCOT and YCWE had no effects on richness (p > 0.10), although MYCOT increased diversity (p = 0.01). Treatment effects on predicted metabolic pathways of fecal microbiota were minimal, suggesting a low impact of MYCOT on fecal microorganisms (p > 0.10).ConclusionContamination of beef cattle diets with multiple mycotoxins altered ruminal and fecal microbial richness, diversity, and metabolic pathways, potentially reducing microbial growth and protein synthesis. YCWE mitigated several of these adverse effects, contributing to partial recovery of disrupted metabolic pathways. This study provides evidence that YCWE counteracts the antimicrobial effects of mycotoxins, offering a practical nutritional strategy to preserve rumen functionality.